Active learning pedagogy transformation: A whole-of-school approach to person-centred teaching and nursing graduates - Fields, Lorraine; Trostian, Baylie; Moroney, Tracey; Dean, Bonnie Amelia (Nurse education in practice, 2021)
In contemporary higher education contexts, active learning pedagogy pervades in discourses around designing quality student experiences. Transposing student bodies from passive to active participants in learning experiences is widely considered best practice in curriculum and pedagogical design. While literature on active learning is vast and recommendations on how to transform into an active learning approach abounds, such advice is often prescribed to individual teachers or courses. What remains unknown in this transformational space is how leadership for person-centred teaching can guide a whole school to shift philosophical presuppositions and take-up active learning as the guiding pedagogy. This paper describes the challenges, processes and steps for how one school, the School of Nursing at an Australian University, invoked transformational change through a philosophical and practice-based shift across all learning spaces (online/ face-to-face/ blended, undergraduate and postgraduate domains). This paper offers recommendations for other schools interested in establishing a whole-of-school commitment to an active learning pedagogy transformation underpinned by person-centred teaching. •Curriculum transformation.•Using the Person-Centred Practice Framework as a underpinning philosophy.•Recommendations for whole School of Nursing involvement.